2023
DOI: 10.1038/s41415-023-5507-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene, mouthwash usage and cardiovascular mortality during 18.8 years of follow-up

Abstract: Aim(s) We tested the following hypotheses: would better oral hygiene self-care (OHS) influence cardiovascular (CVD) mortality? Will using mouthwash in addition to OHS affect CVD mortality? How does mouthwash usage impact the oral microbes? Design and methods Among 354 dentate subjects from the Kuopio Oral Health and Heart study, the association of OHS with CVD mortality was assessed using Cox regression analyses, adjusting for age, sex, smoking, dyslipidemia, diabetes, hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Six studies were randomised control trials (RCTs) ( 34 39 ), 2 studies were case-control studies ( 40 , 41 ), 3 studies were cohort studies ( 42 44 ) and 1 was a stratified prospective study ( 45 ). The geographical locations of these studies include Pakistan ( 34 ), Brazil ( 35 , 37 , 38 ) and China ( 39 ), India ( 40 ), Korea ( 42 , 44 ), Netherlands ( 41 ), USA ( 36 , 43 ), Turkey and Denmark ( 45 ). The included studies had no restrictions on age, gender and socioeconomic status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies were randomised control trials (RCTs) ( 34 39 ), 2 studies were case-control studies ( 40 , 41 ), 3 studies were cohort studies ( 42 44 ) and 1 was a stratified prospective study ( 45 ). The geographical locations of these studies include Pakistan ( 34 ), Brazil ( 35 , 37 , 38 ) and China ( 39 ), India ( 40 ), Korea ( 42 , 44 ), Netherlands ( 41 ), USA ( 36 , 43 ), Turkey and Denmark ( 45 ). The included studies had no restrictions on age, gender and socioeconomic status.…”
Section: Resultsmentioning
confidence: 99%
“…Combining these oral hygiene practices further reduced the risk of HF ( P = 0.024). Additionally, Oral hygiene self-care (OHS) (twice/day brushing, regular flossing and mouthwash usage) was also studied in 256 patients with and without confirmed diagnosis of coronary artery disease ( 43 ) and reported a significant correlation between better oral hygiene (brushing with flossing) and reduced the risk of CVD mortality by 51% (HR 0.49, p = 0.01), those who had coronary artery disease at baseline showed a marginally significant benefit (HR 0.50, p = 0.07). However, mouthwash usage did not have any effect on OHS (HR = 0.49, p = 0.01), indicating no additional benefits nor detriments during the 18.8 years of follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was noted that individuals who demonstrated better oral hygiene had notable survival advantages concerning mortality caused by CVDs. 48 …”
Section: Cvd and Pd Associationmentioning
confidence: 99%
“…Additionally, it was noted that individuals who demonstrated better oral hygiene had notable survival advantages concerning mortality caused by CVDs. 48 To examine the potential systemic effects of periodontal therapy timing, Graziani et al 49 compared root planing and scaling administration within a 24-hour timeframe to root planing and scaling done over four weeks. The impact of both treatment regimens on inflammatory markers was additionally assessed.…”
mentioning
confidence: 99%
“…There is therefore a good chance that many oral health professionals (dentists, dental therapists, oral hygienists, dental specialists) will encounter such patients in their private or public dental clinics. Barrak and colleagues (2023) 1 have highlighted the mismatch between the knowledge and skill requirement of the general dental practitioner (GDP) in managing such patients and the training provided at undergraduate (UG) and general postgraduate (PG) levels. Studies in the UK among dental schools there and in Ireland have shown that most schools provided lecture-based information with no clinical training at undergraduate level on implant dentistry.…”
Section: What Every Oral Health Practitioner Should Know About How To...mentioning
confidence: 99%